REASSESSING THE ROLE OF ISLAMIC MICROFINANCE FOR FINANCING FUQÂRÂ AND MASÂKIN - Susanti, Vitria (al-'adalah, 2011)
Reassessing the Role of Islamic Microfinance for Financing Fuqârâ and Masâkîn. As a country with the largest number of muslim population in the world, Indonesia sholud consider the high potential of Islamic microfinance. While providing microfinance to the poorest of the poor remains a challenge, lessons learned from Bangladesh experinces can be used to develop new method and strategy that is applicable and suits the condition in Indonesia. It should be taken into account to distinguish the program based on regional and cultural differences as Indonesia consists of such diversity. Furthermore, different social and economy structure in urban and rural requires different treatment to overcome poverty in each area.Keywords: microfinance, poverty, Islamic finance